2016
DOI: 10.7863/ultra.15.05069
|View full text |Cite
|
Sign up to set email alerts
|

Routine Screening for Callosal Dysgenesis in the Second Trimester Is Achievable With Intensive Training

Abstract: Assessing the corpus callosum in the sagittal view is difficult and requires appropriate training and patience; however, this view is feasible without adding substantial time to the examination and provides additional information during a routine second-trimester morphologic scan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The sonographers had not yet been taught the acoustic windows to image the fetal brain structure or the transducer movements to identify the fetal structure. Therefore, the research by Lavender et al 24 provides the first identifiable evidence in ultrasound that supports the theoretical tenet that the creation of a mental schema is an antecedent step to be able to recall and execute the skill safely and efficiently. Credentials are not a replacement for sound pedagogical practice.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The sonographers had not yet been taught the acoustic windows to image the fetal brain structure or the transducer movements to identify the fetal structure. Therefore, the research by Lavender et al 24 provides the first identifiable evidence in ultrasound that supports the theoretical tenet that the creation of a mental schema is an antecedent step to be able to recall and execute the skill safely and efficiently. Credentials are not a replacement for sound pedagogical practice.…”
Section: Discussionmentioning
confidence: 77%
“…For example, when new multi-planar transducer movements are first being acquired, they must first be taught, learned and then consolidated. 13,23 Research by Lavender et al 24 found that sonographers with (variable) skill proficiency required additional clinical skill education and training to be able to image the fetal corpus callosum in the sagittal plane using 2D imaging, at the 18-20-week gestational age morphology scan. The sonographers had not yet been taught the acoustic windows to image the fetal brain structure or the transducer movements to identify the fetal structure.…”
Section: Discussionmentioning
confidence: 99%
“…7 Multiple investigators have reported on the appearance and size of the normal corpus callosum; however, it requires intensive training to accomplish routinely. [8][9][10] Indirect signs may be absent in 60% to 80% of fetuses before 24 weeks' gestation; Paladini et al 3 showed that ventriculomegaly may only be present in 26.5% of cases and colpocephaly in 20.6%. In addition, a midline cystic structure, or cavum-like structure, has been described as present in 58% of cACC cases, increasing the chances of missed diagnoses.…”
mentioning
confidence: 99%
“…In the new 2019 AIUM "Practice Parameter for the Performance of Detailed (High risk) Second‐ and Third‐ Trimester Diagnostic Obstetric Ultrasound Examinations,” the corpus callosum can be evaluated but is not required 7 . Multiple investigators have reported on the appearance and size of the normal corpus callosum; however, it requires intensive training to accomplish routinely 8–10 . Indirect signs may be absent in 60% to 80% of fetuses before 24 weeks' gestation; Paladini et al 3 showed that ventriculomegaly may only be present in 26.5% of cases and colpocephaly in 20.6%.…”
mentioning
confidence: 99%